Telemonitoring heart failure in a remote region: data from cardiac implantable electronic devices. (3rd May 2023) - Duarte, F; Santos, I; Barradas, M; Dourado, R; Martins, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Heart failure (HF) represents an important burden to the medical system attending to its high prevalence and high risk of hospital admissions by decompensations. Remote monitoring (RM) systems using invasive and non-invasive parameters were developed to anticipate clinical deterioration in patients with cardiac implantable electronic devices (CIEDs). Objective: To characterize a cohort of patients with HF and CIEDs in an outermost region. We aimed to accessed data from monitoring device algorithms and to analyze the real impact in clinical decompensations, hospital admissions and all-cause mortality. Methods: Retrospectively multicenter cohort study included 211 patients with HFrEF and CIEDs, between 2010 and 2020. This study population was divided into two specific groups: Group A including patients with RM data and Group B including patients who receive usual care at regular hospital consultations. RM technology applied used different parameters to access the risk of worsening HF and stablishing an alert threshold. Results: Out of 211 patients enrolled, 75% were male and 44.8% were in NYHA functional class II at the time of device implantation. One-hundred and twenty (56.9%) received in-home monitoring system (89% Latitude® and 10.8% Carelink®), corresponding to the Group A. The remaining 91 patients (43.1%) were included in Group B. Forty-nine patients (40.8%) had transvenous implantable cardioverter defibrillator (ICD), 13 (10.8%) had a subcutaneous ICD, 54 (45%) a cardiac resynchronization therapy (CRT) defibrillator and 4 (3.3%) a CRT pacemaker. Group A patients did not have coronary artery disease (p 0.047) and were younger than patients in Group B (median age 66 years, IQR 55 – 73; median age 70 years, IQR 63 – 77). No other statistically differences in main comorbidities were detected between groups. The number of atrial fibrillation (AF) episodes and AF burden was higher in Group A during the follow-up (p 0.006) as well as non-sustained ventricular tachycardia episodes (p 0.016). However, no differences were accessed in emergency department (ED) admissions or heart failure hospitalizations (HFH) by decompensation for patients in group A who received alerts versus patients who not received (p 0.178 and p 0.748, respectively) nor between group A and B (p 0.921 and p 0.213, respectively). Patients in group A had a lower all-cause mortality rate (p < 0.001) and cardiovascular mortality (p 0.002), but no difference in life-threatening ventricular events occurred. Conclusion: In our cohort of HF patients, remote monitoring allowed the premature detection and the correct quantification of arrhythmic events but did not reflect any difference in ED nor HFH by decompensation. Instead, RM system demonstrates ability to reduce global mortality when compared to conventional care. More data about the application of this system and the ideal tracking algorithms are necessary.